Economic dumping: the effects and treatments With special reference to Kurdistan region –Iraq - Noraldin, Shlair (Humanities Journal of University of Zakho, 2023)
The phenomenon of economic dumping is one of the challenges facing the Economics Kurdistan Region _Iraq , as a result of trade liberalization and openness to the outside after 2003 from various countries around the world, especially the neighboring countries, which had a significant negative impact on the economy of the region, hence the importance of Search in shedding light on the concept of economic dumping various types taken both in terms of the motives that countries or companies pay for their exercise, or in terms of duration, and the implications for the practice of dumping policy on the economies of countries that practice this policy and countries where dumping practiced with particular reference Economic flooding in the Kurdistan Region, procedures and treatments for anti-dumping markets in the region, and research found to a set of conclusions and proposals was the most important: the economic dumping in the province is a breakthrough to the markets of the region and controlled by foreign companies. And which led to the weakness of the productive capacity and competitiveness of the domestic product and the closure of many large and small and medium enterprises, and a threat to national security system and economic development in the region in general, and this goes back to the lack of activating the laws and regulations governing the import in the region and the weakness of regulatory agencies on the borders of the region. As the most important proposals to address the effects of dumping, it should adopt the provincial government agricultural policies aimed at creating a comparative advantage in the production of strategic crops .work on the development of agricultural production in quantity and quality using modern technology as well as the development of practical mechanisms for the control of goods and products coming, And conduct the necessary tests in accordance with the indicators of global technical standards to allow it to enter the markets, to protect citizens in the region, and with regard to the industrial sector must support and encourage national industries in the region by providing the appropriate economic environment for these industries.